Pengaruh Dua Susunan dan Kepadatan Lubang Tanam terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau pada Budidaya Vertikultur - Hutauruk, Sixtus; Tarigan, Rio Stepanus; Sinaga, Josafat (AGROSUSTAIN, 2025)
This research aims to determine the effect of two arrangements and density of planting holes on the growth and yield of the kumala mustard variety (Brassica juncea L) in verticulture cultivation. This research was carried out behind the screen house of the Faculty of Agriculture, Santo Thomas Catholic University, Jln. Setia Budi 479 F, Tanjung Sari Medan, North Sumatra Province with an altitude of ± 32 meters above sea level. Starting from May-June 2024. This research used a non-factorial Complete Randomized Block Design (RAKL) consisting of 6 treatments with 3 replications. The treatment factors are P1 = 4 x 12 holes/stem, L1 = 4 x 12 holes/stem, P2 = 4 x 9 holes/stem, L2 = 4 x 9 holes/stem, P3 = 4 x 7 holes/stem, L3 = 4 x 7 Holes/rod. The tools used in this research were pipes (4 inches), saws, machetes, paranets, tape measures, verses, pencils, drink bottles, drills, pottray cups, and wood. The materials used were mustard seeds (kumala variety), wire, soil (soil cleaned of rubbish), water, chicken and goat manure. The research data were analyzed using variance based on a linear model. The effect of the two arrangement treatments and the density of the number of planting holes had no significant influence on the number of leaves, leaf length and fresh weight of plant roots. However, it has a real influence on the height of the green mustard plant, the wet weight per plant and the wet weight of the plant per unit. The best treatment among the other treatments is the L2 treatment (horizontal arrangement with 9 holes.